2018
DOI: 10.1016/j.arth.2017.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Space Suits Increase Particle and Microbiological Emission Rates in a Simulated Surgical Environment

Abstract: Space suits cause increased PER and MER compared with standard surgical clothing. This finding provides mechanistic evidence to support the increased prosthetic joint infection rates observed in clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…Vijaysegaran et al compared particle and microbiologic emission rates from SHS and standard surgical clothing. 10 The authors found higher rates of both particle and microbiologic emission in SHS. Two studies assessed timing of surgical helmet fan activation and concluded that early activation prior to gown dressing increased contamination rates of both the surgeon and scrub nurse.…”
Section: Introductionmentioning
confidence: 94%
“…Vijaysegaran et al compared particle and microbiologic emission rates from SHS and standard surgical clothing. 10 The authors found higher rates of both particle and microbiologic emission in SHS. Two studies assessed timing of surgical helmet fan activation and concluded that early activation prior to gown dressing increased contamination rates of both the surgeon and scrub nurse.…”
Section: Introductionmentioning
confidence: 94%
“… 17 In a recent study comparing particle and microbiological emission rates (PER and MER) between exhaust suits and conventional surgical clothing, exhaust suits had increased PER and MER. 18 While the study is confined to laboratory research, there is a potential risk of contamination to the surgical field due to air emanating from the joints of the suit or turbulence caused by the air expelled from the suit. Additionally, the reduced spatial awareness experienced by surgeons when wearing the suit may lead to inadvertent contamination, emphasizing the need for careful consideration in the use of exhaust suits.…”
Section: Three Main Sources Of Surgical Site Contaminationmentioning
confidence: 99%
“…Concern regarding gown-glove interface contamination has also been reported [52e54]. Two studies examining the New Zealand registry reported that the use of modern exhaust suit systems for primary THA and TKA was not significantly associated with reoperation for infection [55,56], and a paradoxical but nonsignificant trend toward an increased risk of reoperation in the primary TKA subset (odds ratio,1.53; 95% confidence interval,1.00-2.34) [55]. At the second ICM, in the absence of strong evidence, it was concluded that the use of personal protection suits does not reduce the rate of subsequent infection in patients undergoing TJA [57].…”
Section: Personal Protection Suitsmentioning
confidence: 99%